EFEKTIVITAS PIDANA MATI DALAM PENANGGULANGAN KORUPSI DAN IMPLIKASINYA TERHADAP HAK ASASI MANUSIA - Marisa, Kiki (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Corruption in Indonesia is an extraordinary crime that has a systemic impact on social, economic and political life. Although Article 2 paragraph (2) of Law Number 20 Year 2001 provides the legal basis to impose death penalty to the perpetrators of corruption in certain circumstances, until now there has been no real implementation of the provision. This research uses a normative legal approach with a descriptive-analytical method to examine the effectiveness of the death penalty in eradicating corruption and its implications for human rights. The results of the study show that the death penalty is considered to be able to provide a deterrent effect, but its application in the Indonesian legal system is still filled with juridical, moral, and practical obstacles. On the other hand, the application of death penalty has the potential to conflict with the principle of right to life guaranteed by the constitution and international law. Therefore, corruption eradication needs to be carried out through a more comprehensive approach, including bureaucratic reform, anti-corruption education, and law enforcement that is fair and consistent, not just the death penalty.Keywords: Death Penalty, Corruption, Legal Effectiveness, Human Rights, Bureaucratic Reforms